Multidrug-resistant TB in Eastern region of the EU: is the shorter regimen an exception or a rule? - Balabanova,Y; Fiebig,L; Ignatyeva,O; Riekstina,V; Danilovits,M; Jaama,K; Davidaviciene,E; Radiulyte,B; Popa,CM; Nikolayevskyy,V; Drobniewski,F (Thorax, 2017)
WHO recently recommended the use of a shorter multidrug-resistant TB (MDR-TB) regimen under programmatic conditions. We assessed eligibility for this regimen in a cohort of 737 adult patients with MDR-TB from Latvia, Lithuania, Estonia and Bucharest city recruited in 2007 and 2009. Only 4.2% of the patients were eligible for this regimen. Ethambutol (64%), pyrazinamide resistance (58%) and previous exposure to second-line TB drugs were major reasons for non-eligibility. High-level resistance to isoniazid is expected due to widespread prevalence of katG mutations. In Eastern Europe, the use of the shorter regimen might be an exception rather than a rule.